Asset Liability Management of Conventional and Islamic Banks in Malaysia - Loon Mun, Yee; Mohd Thas Thaker, Hassanudin (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2017)
The objective of the paper is to investigate the effect of asset liability management on the financial performance of 6 conventional and 6 Islamic banks in Malaysia during the period of 2010 to 2013. The variables used in the study are capital adequacy, asset quality, management efficiency, earnings quality, liquidity, size of bank and degree of risk aversion in relation to asset liability management to examine the return on equity (ROE), which is the measure of profitability of the banks. The quantitative analysis using correlation and regression analysis concluded that there is a positive relationship between asset liability management and the financial performance of the banks.DOI: 10.15408/aiq.v9i1.3334